A Study on Students' Perceptions of Digital Sandbox Games for English Vocabulary - Anshory, Syam All; Wulandari, Sri; Asyhar, Wildan Isna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2025)
This study investigates junior high school students' perceptions of using digital sandbox games to improve their English vocabulary. As traditional rote memorization methods often fail to engage